Lung Cancer in a Sample of Iraqi Patients - Al-Rahim, Yousif A. (AL-Kindy College Medical Journal, 2007)
Background: Lung cancer is responsible for the mostcancer deaths in both men and women throughout theworld. Deaths from lung cancer (160,440 in 2004,according to the National Cancer Institute) exceed thenumber of deaths from four other major cancers combined(breast, colon, pancreatic and prostate).Objective: To assess the behavior and the approaches oflung cancer in a sample of Iraqi patients.Methods: This descriptive retrospective study wasperformed using the records of 390 patients proved to havelung cancer that had attending the Thoracic SurgeryDepartment of Surgical Specialties Hospital-Medical City\Baghdad for the period from January, 1st, 2001 toDecember, 31st,2002.Results: The results of this study revealed that 71.8% ofthe patients were male, with a mean age of 63 years. Themajority of the patients (90.2%) were smokers, the numberof cases increases with the increase in the duration ofsmoking or the amount of daily cigarette smoking.Radiotherapy is the primary management of 75.9% and thesurgical choice was in 24.1% of the patients, but thetumors were removed only in 42.5% of operable patients.Conclusions: Lung cancer is an important and seriouspublic health problem with an increasing in incidence andprevalence in Iraq; cough is the most common clinicalfinding, found in 98.5% of patients, followed byhaemoptysis (64.1%); cigarette smoking is responsible forthe at least 90% of its etiology. Sequamous cell carcinomais the most common type of primary lung cancer in Iraq(42.6%) with prominence in male gender; adenocarcinomais the second common type with equal distribution in maleand female